Analisis waste pada depo rawat jalan dengan menggunakan lean hospital di Rumah Sakit Islam Siti Hajar Mataram - Fauzi, Lalu Rizki; Anggraini, Eniza (Universitas Mataram, 2024)
Pharmaceutical installations can provide substantial revenue if managed properly and efficiently. Good or bad service can affect patient satisfaction. For this reason, pharmaceutical installations must improve quality in terms of patient satisfaction, one of which is by reducing waste that occurs in the pharmaceutical service process in hospitals. This study aims to analyze what waste occurs in outpatient depot services to improve service efficiency. This research is descriptive qualitative. Data were obtained through document review, direct observation, interviews.Â Waste identification uses Value Stream Mapping and Fishbone Diagram to determine the root causes of critical waste that occurs. The results showed that the highest percentage of value added was in the ordinary prescription service of 63.41%, the highest percentage of necessity but non-value added was in the prescription service that required drug distribution from the warehouse unit of 70.79%, and the highest non-value added was in the compounded prescription service process of 36.59%. By using lean hospital, it can be identified that many wastes occur including waiting, transportation, and defects. Increasing service efficiency at the Siti Hajar Mataram Islamic Hospital Outpatient depot can be done by minimizing non-value added activities.